The last kingdom. [Series 1] [videorecording (DVD)] - Murphy, Nick; Byrne, Anthony, 1975-; Dreymon, Alexander, 1983-; Dawson, David, 1982-; Cox, Emily, 1985-; Cornwell, Bernard (BBC Worldwide Ltd. Program, 2016)
The re-telling of the valiant story of King Alfred the Great and his desire to unite many separate kingdoms into what would become England. Combining real historical figures and events with fictional characters, it is the story of how a people reclaimed their land from the invading Vikings and built a place they call home.